2008
DOI: 10.1038/modpathol.2008.121
|View full text |Cite
|
Sign up to set email alerts
|

The expression of NeuroD and mASH1 in the gastroenteropancreatic neuroendocrine tumors

Abstract: Gastroenteropancreatic neuroendocrine tumors are uncommon and their tumor biology has not been well elucidated to date. Currently the WHO classification is widely used for the diagnosis and distinction of this tumor entity, which is sometimes cumbersome. Although neuroendocrine tumor markers do exist (ie chromograninA, synaptopyhsin, etc), sensitive and specific markers that accurately predict tumor growth and tumor behavior are still absent. In the present study, we assessed the expression of transcription fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…MASH1, also known has human achaetescute homolog-1, is a transcription regulator that plays an important role in brain development and the diffuse neuroendocrine system including adrenal medullary chromaffin cells, thyroid parafollicular C cells, glomus chief cells, and pulmonary neuroendocrine cells. 11,21,45 Although immunohistochemical expression of MASH1 has been reported in pulmonary neuroendocrine neoplasms 9,12,13,29 and gastrointestinal endocrine neoplasms 27,37 consistent with the protein's biology, the immunoreactivity in neoplasms derived from adrenal medullary chromaffin cells (pheochromocytoma) and the adrenal cortex has not been previously explored. We hypothesized that MASH1 might be another useful marker of pheochromocytoms; however, despite strong nuclear positive control staining using a pulmonary small cell carcinoma, MASH1 expression was not seen in any pheochromocytoma (0 of 35) or adrenal cortical lesion (0 of 63).…”
Section: Discussionmentioning
confidence: 96%
“…MASH1, also known has human achaetescute homolog-1, is a transcription regulator that plays an important role in brain development and the diffuse neuroendocrine system including adrenal medullary chromaffin cells, thyroid parafollicular C cells, glomus chief cells, and pulmonary neuroendocrine cells. 11,21,45 Although immunohistochemical expression of MASH1 has been reported in pulmonary neuroendocrine neoplasms 9,12,13,29 and gastrointestinal endocrine neoplasms 27,37 consistent with the protein's biology, the immunoreactivity in neoplasms derived from adrenal medullary chromaffin cells (pheochromocytoma) and the adrenal cortex has not been previously explored. We hypothesized that MASH1 might be another useful marker of pheochromocytoms; however, despite strong nuclear positive control staining using a pulmonary small cell carcinoma, MASH1 expression was not seen in any pheochromocytoma (0 of 35) or adrenal cortical lesion (0 of 63).…”
Section: Discussionmentioning
confidence: 96%
“…Carcinoids/ NETs are said to be derived from neuroendocrine cells dispersed mainly in the bronchial and GI tracts. Several reports have revealed that some basic helix-loop-helix transcription factors, which are critical in neural differentiation, contribute to enteroendocrine cell differentiation and that NENs including carcinoids/NETs express these factors [28][29][30] . Our data support the relationship between neural differentiation and carcinoid/NET tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of Ascl1 expression have been observed in a wide range of neuroendocrine tumors, including small cell lung carcinomas (Ball 2004), prostate tumors (Vias et al 2008), medullary thyroid cancers (Chen et al 2005), and gastroenteropancreatic tumors (Shida et al 2008). A direct role of Ascl1 in neurodendocrine tumor formation is supported by experiments of overexpression of Ascl1 together with SV40 Large T Antigen in lung epithelium, which produce massive neuroendocrine tumors (Linnoila et al 2000), and Ascl1 knockdown experiments, which inhibit proliferation of lung cancer cells both in vitro and in vivo (Osada et al 2005;Jiang et al 2009).…”
Section: Ascl1 Promotes Cell Divisions In the Embryonic Brain And Ns mentioning
confidence: 99%